Momentum Accounting and Managerial Goals on Impulses - Ijiri, Yuji (Management Science, 1988)
Conventional accounting measures wealth W (assets and liabilities) and accounts for its net change, W(t + 1) − W(t), by means of income ΔW(t), classified into various revenue and expense items. Proposed “momentum accounting” measures income momentum Ẇ = dW/dt (time rate at which income is being earned at a given point in time) and accounts for its net change, Ẇ(t + 1) − Ẇ(t), by means of impulses ΔẆ(t). Here the impulses, a term borrowed from the momentum-impulse principle in mechanics, are classified into various factors, internal or external to the enterprise, that contributed to the momentum change. If conventional accounting is viewed as focusing on an odometer of a car, momentum accounting is analogous to focusing on its speedometer and attributing the change in its reading to impulses that are judged to be responsible for the change. This paper proposes impulse-based managerial goals as a substitute for currently popular income-based managerial goals, discussing problems associated with the latter that highlights short-term income achievements and that tends to reward management for the momentum created by their predecessors as it is realized as income by the mere passage of time.